NQO1 rs1800566 C>T polymorphism was associated with a decreased risk of esophageal cancer in a Chinese population. (March 2014) - Yin, Jun; Wang, Liming; Wang, Xu; Zheng, Liang; Shi, Yijun; Shao, Aizhong; Tang, Weifeng; Ding, Guowen; Liu, Chao; Liu, Ruiping; Chen, Suocheng; Gu, Haiyong
Abstract Background. Esophageal cancer was the fifth most commonly diagnosed cancer and the fourth leading cause of cancer-related death in China in 2009. Esophageal squamous cell carcinoma (ESCC) accounts for more than 90% of esophageal cancers. Genetic factors may play an important role in the carcinogenesis of ESCC. Methods. We conducted a hospital-based case–control study to evaluate functional NAD(P)H:quinone oxidoreductase 1 (NQO1) rs1800566 C>T and NQO2 rs2070999 G>A single-nucleotide polymorphisms on the risk of ESCC. A total of 629 patients with ESCC and 686 controls were recruited for this study. The genotypes were determined using the ligation detection reaction method. Results. When the NQO1 rs1800566 CC homozygote genotype was used as the reference group, the TT genotype was associated with a significantly decreased risk of ESCC. In the recessive model, when the NQO1 rs1800566 CC/CT genotypes were used as the reference group, the TT homozygote genotype was associated with a 31% decreased risk of ESCC. A significantly decreased risk of ESCC was evident in patients with the NQO1 rs1800566 C>T polymorphism among females, those of a younger age (<63 years), those who had never smoked, those who consumed alcohol and those who did not. There was no association found between the NQO2 rs2070999 G>A polymorphism and ESCC risk. Conclusion. The NQO1 rs1800566 TT genotype was associated with a decreased risk of ESCC in a Chinese population. The association was evident among female patients, younger patients, patients who had never smoked, patients who consumed alcohol and those who did not. These findings need to be confirmed by repeating the study in a larger cohort of patients.